Relationship between twelve mechanic measures and score for national-level pistol shooters - Hawkins, R.; Bertrand, P. (International Journal of Performance Analysis in Sport, 2015)
The relationship between shooting mechanic measures and performance was determined by combining data from two pools. Eight national-level air-pistol athletes performed 60 simulated competition shots from each of four stance angles (0, 15, 30, and 45 degrees). A different pool of eight national-level shooters performed 60 simulated competition shots from each of two spine-to-arm angle positions (70 and 90 degrees). NOPTEL optoelectronic system was used to collect data for 12 mechanic measures from both pools.